Automotive workers: the role of coordinative and conditional abilities as effectiveness wellness indicator - Rodio, Angelo; Di Libero, Tommaso; Biffi, Alessandro; Fernando, Fredrick; Fattorini, Luigi (Frontiers in Public Health, 2024)
Noncommunicable diseases are increasing due to sedentary and unhealthy lifestyles. The World Health Organization and the American College of Sports Medicine recommend a healthy diet and regular physical activity, particularly in the workplace. Prolonged and repetitive work tasks can result in extended sick leave and decreased productivity while at work. Therefore, it is important to identify predictive factors that can act as indicators of the health status of employees. Utilizing motor abilities assessment tests can help to identify health issues at an early stage. Promoting preventive health measures is crucial to addressing chronic diseases and enhancing overall occupational well-being. The purpose was to characterize workers' motor abilities and fitness levels and identify potential indicators. A total of 606 workers took part in this study, including 529 men with a height of 176±0.09cm and body mass of 75.9±14.1kg, as well as 77 women with a height of 162±0.11cm and an average body mass of 58.9±11.1kg. These individuals were enrolled during an Italian automotive corporation's mandatory annual medical check-up. The participants were categorized into three groups based on their occupational roles: blue collar, manager, and white collar groups. Participants underwent motor abilities assessment tests for upper-limb strength, trunk flexibility, and reaction time. Blue collar reported the best results in upper-limb strength (93.3kgf±18.60), but worse in flexibility (21.7cm±7.90), and reaction time total time (58.8s±4.74;) and average intermedium (0.68ms±0.11). The white collar group shows the best result in flexibility (23.7cm±8.94) and reaction time (48.5s±4.38; 0.64ms±0.09). Despite being frequently used to assess health status, hand grip measurements may not provide accurate differentiation because of the common use of blue collar workers for tasks requiring upper-limb strength. In contrast, reaction time metrics appear more reliable and discriminative in evaluating a worker's physical fitness.